O kriteriyakh kompetentnosti spetsialistov v oblasti sportivnogo marketinga - Smolyanov, P.; Shilboury, D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
This research examined sport marketing competencies considered by 103 professionals to be important for sport marketing administrators. Four job segments within the profession were surveyed and included: sport marketing firms, amateur sport organizations, professional sport organizations, and college athletics.